Hypoglycemic and toxic effects of saponins from the fruit of bitter apple [Citrullus colocynthis (L.) Schrad] on the internal organs of Norway rat [Rattus norvegicus (Berkenhout)] - Alias, Ehab E. Alias; Zeinelabdin, Mohamed; Bashir, Nabil; Assad, Yousif; Abdelbagi, Omer (Gezira Journal of Agricultural Science, 2015)
Nowadays, natural products receive attention  to research centers because  of  their special importance  in  safety  of communities. The  curative  properties  of  these plants are  mainly due to the presence of various complex chemical substances of different composition which occur as secondary metabolites.The main objectives of this study were to evaluate saponins toxic effects as reflected in the  histopathological changes in the internal organs of Norway rats and to study the hypoglycemic effects induced by the same group. Powdered dried fruit parts (rinds, pulps and seeds) of bitter apple were screened for detection of saponins, glycosides, terpenes, anthraquinones, flavonoids, tannins, alkaloids, coumarins, cardiac glycosides, cyanogenic glycosides and cucurbitacins. The results of the qualitative analysis and phytochemical screening profiles indicated that, most of the natural products tested for were present in the plant material, except cyanogenic glycosides. Crude saponins were extracted from the rind and their acute toxicity was determined on Norway rats. Five dosage levels (60, 70, 80, 90 and 100 mgs saponins/rat) were administered intraperitoneally   to each batch of albino rats (4 rats/batch). The histological changes in the liver exhibited prominent nucleolus, open chromatin, congestion of central veins and liver sinusoids. The kidney showed signs of reduced renal tubules and lining of epithelial cells. The stomach and digestive system showed mucosal edema, open chromatin, prominent nucleolus and structural necrosis. Percentages reduction in glucose level  in treated rats and the control after six hours were 42%, 55.4%, 60%, 62.5%, 69.3 and 0.10 %, following the same order. There was a considerable dose-dependent decrease in the mean concentration of glucose in the plasma of the treated rats. أصبحت المنتجات النباتية الطبيعية في الآونة الأخيرة محوراً مهماً للبحث في الكثير من المراكز البحثية، وذلك لأهميتها الخاصة في سلامة المجتمعات. تعود الخواص العلاجية لهذه النباتات لاحتوائها على العديد من المركبات الكيمائية المعقدة ذات التراكيب المتباينة والتي توجد فيها على صورة نواتج ثانوية لعملية الأيض. هدفت هذه الدراسة إلي  تقويم الآثار الخافضة للسكر والآثار السامة لصابوينات الحنظل والتغيرات النسيجية التي تحدثها على الأعضاء الداخلية للجرذ النرويجي. تم كل ذلك عبر عدة طرق هدفت للكشف عن وتسمية مجاميع المواد الفاعلة في مسحوق ثمار نبات الحنظل   C.colocynthis  (L.)Schradوشملت هذه المواد الصابونينات، الجلايكوسيدات والفلافونويدات والقلويدات والأنثروكينونات، والتربينات والتانينات والكومارينات، الجلايكوسيدات القلبية والجلايكوسيدات والسيانوجينية والكيوكيربتسينات. كانت النتائج كلها إيجابية مع غياب الجلايكوسيدات السيانوجينية. تم اختبار السمية الحادة للصابونينات المستخلصة من قشور ثمار نبات الحنظل علي طريق الحقن عبر الغشاء البروتوني للجرذان النرويجية البهقاء  Rattus norvegicus  ( Berkenhout). بناءً على تجارب أولية تم اختبار خمس جرعات وهى 60 ، 70، 80، 90 و100 مجم صابونين خام/جرذ. فيما يختص بالتغيرات النسيجية على الأعضاء والأنسجة الداخلية للجرذان المعاملة بالصابونين فقد لوحظ أنها شملت تشوه الأنوية وانفتاح الكروماتين واحتقان الأوردة في خلايا الكبد مع انخفاض الخلايا الطلائية المبطنة للأنيبيبات البولية في الكلى. أما بالنسبة للتغيرات في المعدة والجهاز الهضمي فشملت وزمة الغشاء المخاطي، وانفتاح الكروماتين مع تشوه الأنوية وموت الأنسجة. تمت أيضا  دراسة أثر الصابونينات علي خفض معدل السكر في دم الجرذان المعاملة بالجرعات السابقة وكذا الشاهد حيث تم أخذ متوسط النسب المئوية لانخفاض السكر في الدم خلال ست ساعات  وكانت المتوسطات42% ، 55.4%، 60%،62%، 69.3%، 0.10% وللشاهد على الترتيب. وقد لوحظ أن هنالك تدني ملحوظ في نسبة الجلوكوز في دم الجرذان المعاملة يتناسب عكسياً مع الجرعة المستخدمة.